Mapping the Evolution: A Bibliometric Dive into TPACK Research Trends (2020-2023) - Helingo, Adimawati; Nurpahmi, Sitti (English Education Department, 2024)
The purpose of this study is to present the research trends within Technological Pedagogical Content Knowledge (TPACK) in English Language Teaching (ELT) from 2020 through August 3rd, 2023. Data for this bibliometric study were collected from Google Scholar by filtering publications that mentioned TPACK in ELT. A maximum of 770 papers were mined to quantify how the overall number of publications, citation counts and keyword co-occurrence varied. Taken together, the results show a clear rise in TPACK related publications over this four-year period that mirrors the heightening need to embed technology into teaching language worldwide but especially due to responses around Covid 19 and remote hybrid learning environments. Citation analysis demonstrates influential works on what factors are important in technology use and impacts. The second step of the co-occurrence analysis points to central themes such as pedagogical content knowledge and technology integration which are already emphasized in research literature, alongside an emerging dynamic perspective on COVID-19 impact for teaching practices. These results deeply emphasize the importance of future research targeting towards methodological clarity in TPACK investigations. This study contributes immensely to education and research because it reveals that TPACK plays critical roles in tackling these challenges/opportunities that have been brought about by the adoption of technological advancement when teaching a language.